2013
DOI: 10.1371/journal.pone.0064821
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ALK Rearrangement in Chinese Non-Small Cell Lung Cancer Using FISH, Immunohistochemistry, and Real-Time Quantitative RT- PCR on Paraffin-Embedded Tissues

Abstract: Patients with ALK gene rearrangements often manifest dramatic responses to crizotinib, an ALK inhibitor. Accurate identification of patients with ALK-positive non-small cell lung cancer (NSCLC) is essential for the clinical application of ALK-targeted therapy. However, assessing EML4-ALK rearrangement in NSCLC remains challenging in routine pathology practice. The aim of this study was to compare the diagnostic accuracy of FISH, immunohistochemistry (IHC), and real-time quantitative RT-PCR (QPCR) methodologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 23 publications
7
44
0
Order By: Relevance
“…The incidence of ALK rearrangements was found to be 9.6% (73/763) in NSCLC and 11.0% (54/493) in adenocarcinoma in our study, which was similar to the results previously published in Chinese (Shan et al, 2014;Wang et al, 2014a;Yang et al, 2014) and Asian cohorts (Kim et al, 2014). As previously reported, patients who were ALK-positive were predominantly young women and never/light smokers (Lynch et al, 2004;Rodig et al, 2009;Shaw et al, 2009;Wong et al, 2009;Jokoji et al, 2010;Takahashi et al, 2010;Zhang et al, 2013;Zhang et al, 2014). In our study, young age, female gender, and never-smokers were significantly associated with ALK rearrangement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The incidence of ALK rearrangements was found to be 9.6% (73/763) in NSCLC and 11.0% (54/493) in adenocarcinoma in our study, which was similar to the results previously published in Chinese (Shan et al, 2014;Wang et al, 2014a;Yang et al, 2014) and Asian cohorts (Kim et al, 2014). As previously reported, patients who were ALK-positive were predominantly young women and never/light smokers (Lynch et al, 2004;Rodig et al, 2009;Shaw et al, 2009;Wong et al, 2009;Jokoji et al, 2010;Takahashi et al, 2010;Zhang et al, 2013;Zhang et al, 2014). In our study, young age, female gender, and never-smokers were significantly associated with ALK rearrangement.…”
Section: Discussionsupporting
confidence: 92%
“…Recently many studies have reported the efficacy of Ventana IHC for detecting ALK rearrangements with D5F3 antibodies and have supported that Ventana IHC is a method with excellent sensitivity and specificity to identify ALK rearrangements in paraffin-embedded lung cancer specimens (Takahashi et al, 2010;Zhang et al, 2013;Shan et al, 2014;Wang et al, 2014a;Zhang et al, 2014). The sensitivity and specificity of Ventana IHC were found to be 100 and 98.2%, respectively, and the concordance rate between the fluorescence in situ hybridization (FISH) and the Ventana IHC was 98.4% (Wang et al, 2014a).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the current real-world study, the characteristics of patients were consistent with those reported in previous studies (16,17). More specifically, ALK rearrangement occurred in relatively young patients, >50% of the patients had no history of smoking and almost all patients were diagnosed with adenocarcinoma.…”
Section: Discussionsupporting
confidence: 88%
“…The amplicons can be sequenced to identify the specific fusion variants. [63][64][65] The RT-PCR method is targeted to one partner gene per run; it is limited to the primer sequence located on the partner gene and ALK gene. Quantitative RT-PCR can detect mRNA amount differences, which are appropriate to test overexpression of fusion and non-fusion ALK.…”
Section: Alk Diagnostic Methods and Target Cancer Therapymentioning
confidence: 99%